New species of Notalina Mosely, 1939 (Trichoptera: Leptoceridae) from Chapada Diamantina National Park, Northeast Brazil, with new records of other leptocerids from the Caatinga biome - Ana L. Henriques-Oliveira; André A. Alves; Felipe F.F. Moreira (European Journal of Taxonomy)
The genus Notalina Mosely, 1939 contains 29 species divided into two subgenera: Notalina (Notalina) Mosely, 1939, which includes 15 endemic species from Australia and Tasmania, and Notalina (Neonotalina) Holzenthal, 1986, which comprises 14 species exclusively from South America. In Brazil, eleven species have been recorded, with the main distribution areas in the Cerrado and Atlantic Forest biomes of the Southeast and Central-West regions, while only three species have been recorded in the Northeast region. In this paper, we describe and illustrate two new species of Notalina (Neonotalina), Notalina (Neonotalina) diamantina sp. nov. and Notalina (Neonotalina) daniae sp. nov., from Chapada Diamantina National Park, Bahia, Northeast Brazil. We also provide new distributional records for other leptocerids from the Caatinga biome.